Intelligent Wind-speed Monitoring System Based on the Zigbee Wireless Network - Lu, Zhongliang; Li, Yujiang; Fu, Teng (International Journal of Online and Biomedical Engineering (iJOE), 2015)
In the use of traditional mechanical or electronic handheld anemometer, surveyors must measure wind speed in the prescribed measuring route, so it is easy to miss part of measurement or records, etc. The monitoring system uses CC2530 as the master controller, and calculates the value of wind speed by means of optical pulse emitted by an optical coupler. Different nodes are arranged on the wall of roadway, to set up a Zigbee network. When the surveyor’s anemometer node transmit the measured value of wind speed to the fixed nodes of the roadway, the system will make use of the RSSI to calculate the coordinates of the surveyor, and data package be sent to the network coordinator and to the upper computer with the aid of optical fiber. The system can rapidly and accurately record the value of wind speed and the position of surveyors, to ensure the safety of surveyors.